Optical properties of π-conjugated donor-acceptor systems with controlled hyperpolarizability - Piryatinski, Yu.P.; Sevryukova, M.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
For supramolecular compounds with donor and acceptor fragments, coupled with each other by the π-conjugated methyn chain, it was ascertained an influence of Cl and Br atoms on the π-conjugation and charge transfer in them in molecular and aggregate states. Compound, which contains Br atom, crystallizes into a noncentrosymmetric polar structure and under infrared (1064 nm) laser excitation it is observed the second harmonic generation and intense up-conversion photoluminescence in the visible spectral region. For compounds containing Cl atom, when passing into a crystalline state, only up-conversion photoluminescence is observed, which can be considered as twophoton excited. Possible mechanisms of intramolecular charge transfer and collective interactions in investigated molecular structures under one- and two-photon excitation are considered.